Physical Activity, Cognitive Decline, and Quality of Life in Older Adults - Faraziani, Fateh; Eken , Özgür (International Journal of Sport Studies for Health, 2024)
Objective: This narrative review aims to explore the relationship between physical activity, cognitive decline, and quality of life in older adults, examining the mechanisms by which PA influences these outcomes, summarizing key studies, and identifying differences in impact by type, duration, and intensity of PA. Methods and Materials: A comprehensive literature search was conducted across multiple electronic databases, including PubMed, MEDLINE, Scopus, and PsycINFO. Inclusion criteria focused on studies involving participants aged 60 and older, examining the effects of PA on cognitive function and QoL, published in English between January 2000 and December 2023. Results: Physical activity positively impacts cognitive decline and QoL in older adults through improved cardiovascular health, increased neuroplasticity, and enhanced neurogenesis. Key studies indicate that regular PA, especially aerobic and resistance exercises, is associated with better cognitive functioning and slower cognitive decline. The type, duration, and intensity of PA significantly influence its effectiveness, with moderate-intensity and long-term engagement yielding the most substantial benefits. Conclusion: Physical activity is a vital intervention for promoting cognitive health and enhancing QoL in older adults. Healthcare providers and policymakers should encourage regular PA among older adults, incorporating a variety of exercises to maximize benefits. Future research should focus on establishing causality, exploring optimal PA regimens, and examining the cost-effectiveness of PA programs to inform practice and policy.